Caspase-8 contributes to angiogenesis and chemotherapy resistance in glioblastoma - Fianco, Giulia; Mongiardi, Maria Patrizia; Levi, Andrea; De Luca, Teresa; Desideri, Marianna; Trisciuoglio, Daniela; Del Bufalo, Donatella; Cinà, Irene; Di Benedetto, Anna; Mottolese, Marcella; Gentile, Antonietta; Centonze, Diego; et al. (eLife, 2017)
Caspase-8 is a key player in extrinsic apoptosis and its activity is often downregulated in cancer. However, human Caspase-8 expression is retained in some tumors, including glioblastoma (GBM), suggesting that it may support cancer growth in these contexts. GBM, the most aggressive of the gliomas, is characterized by extensive angiogenesis and by an inflammatory microenvironment that support its development and resistance to therapies. We have recently shown that Caspase-8 sustains neoplastic transformation in vitro in human GBM cell lines. Here, we demonstrate that Caspase-8, through activation of NF-kB, enhances the expression and secretion of VEGF, IL-6, IL-8, IL-1beta and MCP-1, leading to neovascularization and increased resistance to Temozolomide. Importantly, the bioinformatics analysis of microarray gene expression data derived from a set of high-grade human gliomas, shows that high Caspase-8 expression levels correlate with a worse prognosis. Cancer cells are different to normal cells in various ways. Most cancer cells, for example, delete or switch off the gene for a protein called Caspase-8. This is because this protein is best known for promoting cell death and stopping tumor cells from growing. However, some cancers keep the gene for Caspase-8 switched on including glioblastoma, the most aggressive type of brain cancer in adults. This begged the question whether this protein may in fact promote the development of tumors under certain circumstances. Glioblastomas are often highly resistant to chemotherapy and can communicate with nearby cells using proteins called cytokines to promote the formation of new blood vessels. The new blood vessel allows the tumor to readily spread into healthy brain tissue, which in turn makes it difficult for surgeons to remove all the cancerous cells. As a result, glioblastomas almost always return after surgery, and so there is strong need for new effective treatments for this type of cancer. Fianco et al. have now investigated whether Caspase-8 helps glioblastomas to grow and form new blood vessels. One common method to study human cancer cells is to inject them into mice and watch how they grow, because these experiments mimic how tumors develop in the human body. When mice were injected with human glioblastoma cells with experimentally reduced levels of Caspase-8, the cells grew poorly and did not form as many new blood vessels as unaltered glioblastoma cells. Further experiments showed that, when grown in the laboratory, glioblastoma cells with less Caspase-8 were more sensitive to a chemotherapeutic drug called temozolomide. These findings confirm that Caspase-8 does boost the growth and drug resistance of at least one cancer. When Fianco et al. analyzed clinical data from patients affected by glioblastoma, they also observed that those patients with high levels of Caspase-8 often had the worse outcomes. Previous studies conducted in white blood cells showed that Caspase-8 activated a protein complex called NF-kB, which in turn led to the cells releasing cytokines. Fianco et al. have now verified that Caspase-8 promotes NF-kB activity also in glioblastoma cells, and that this causes the cancer cells to release more cytokines. As such, these findings reveal a clear link between Caspase-8 and the formation of new blood vessels by glioblastomas. Future studies are now needed to understand why Caspase-8 promotes cell death in some cancers but the formation of new blood vessels in others. Indeed, Caspase-8 might become a target for new anticancer drugs if it is possible to inhibit its cancer-boosting activity without interfering with its ability to promote cell death.